Reduplikasi Bahasa Jawa dalam Cerbung Langit Jingga Karya Sumono Sandy Asmoro - Fahningrum, Eksa Dewi; Indrayanto, Bayu (Jurnal Bahasa dan Sastra, 2025)
This study discusses the forms and meanings of reduplication in Javanese found in the short story Langit Jingga by Sumono Sandy Asmoro, published in Panjebar Semangat magazine, edition 8, 2008. The study aims to describe the types of reduplication and their meanings in the short story. The research method used is descriptive qualitative, with content analysis techniques and data collection through observing and note-taking. The results of the study found five forms of Javanese reduplication: 1) full reduplication of the base word, 2) reduplication with changes in sound or phonemes, 3) reduplication with affixes, 4) partial reduplication of the base word, and 5) reduplication of the final syllable. The meanings of reduplication found in the short story are: 1) indicating more than one, 2) meaning resemblance, 3) meaning a small amount, and 4) meaning the highest or superlative.